An electrochemical study on the influence of sodium molybdate on electrodeposition process and phase composition of ternary Zn–Ni–Mo alloy coatings. (27th October 2015) - Winiarski, J.; Laszczyńska, A.; Szczygieł, B.
Abstract : Ternary Zn–Ni–Mo alloy coatings were deposited from a citrate-sulphate bath at pH 5.7 containing different amounts of sodium molybdate. The content of molybdenum in the coatings (from 0.3 to 5.2 at.-%) can be easily controlled by increasing sodium molybdate concentration in the plating bath from 0.0025 to 0.05 mol dm − 3, which results also in deposition of smoother deposits. An increase in molybdate concentration leads to the shift of reduction potentials towards more negative values and to the decrease in current efficiency of deposition process. XRD analyses and anodic linear sweep voltammetry (ALSV) measurements demonstrated that at least two phases are formed in the Zn–Ni–Mo alloy: a hexagonal zinc phase or solid solution of nickel in zinc and Ni5 Zn21 intermetallic compound. Furthermore, the XRD analyses revealed a third phase, which could be assigned to the oxidised species of molybdenum or other alloying metals.